Up close it feels dangerous: 'anxiety' in the face of risk - Thomas M. Eisenbach; Martin C. Schmalz (Federal Reserve Bank of New York, 2013)
Motivated by individuals' emotional response to risk at different time horizons, we model an 'anxious' agent - one who is more risk averse with respect to imminent risks than distant risks. Such preferences describe well-documented features of 1) individual behavior, 2) equilibrium prices, and 3) institutions. In particular, we derive implications for financial markets, such as overtrading and price anomalies around announcement dates, as well as a downward-sloping term structure of risk premia, which are found empirically. Since such preferences can lead to dynamic inconsistencies with respect to risk trade-offs, we show that costly delegation of investment decisions is a strategy used to cope with 'anxiety.'
Keywords: D01; D03; D81; G02; G11; G12; 330; risk aversion; dynamic inconsistency